Poprzez refleksję do postawy refleksyjnej prz yszłego naucz yciela jęz yka obcego – trudności interpretacyjne badania w działaniu - Stańczyk, Joanna (Neofilolog, 2010)
This article is an attempt to determine the reasons for difficulties encountered in the interpretation of data collected in the process of conducting action research on developing a reflective attitude in TTC students. The starting point for investigating the above issue is a short presentation of the action research study: the subjects’ aim, and tools employed in the process. The difficulties with interpreting the collected data will be examined mainly from the cognitive perspective, as the description and interpretation relate to internal cognitive processes, observable only in potential change of behaviour. It is significant, therefore, to work out, among the research participants, a coherent conceptual area referring to the changes under investigation. Interpretation of data is also the result of the quality of interactions among the research participants, which will be presented using the example of relations between the teacher researcher and participant-students and their possible influence on the students’ opinions. The article closes with suggestions for selecting criteria for the interpretation of data being collected.